Development of practicum-based mobile augmented reality through the group investigation model to improve students' creative thinking - Wiwi Wikanta; Peni Suharti; A. Asy’ari (University of Muhammadiyah Malang, 2023)
Students' creative thinking skills need to be developed, one of which is through learning. This research was aimed to produce Augmented Reality (AR) media based on Group Investigation (GI) practice models on various living things to improve students' creative thinking skills. This research and development using the 4-D model. However, it only reached the Develop stage. The population of this study was students of SMA Muhammadiyah 10 Surabaya in the Science class, with 37 students in each class. This study collected data through validation tests, pre-tests, post-tests, observation sheets for creative thinking skills, questionnaires, and student responses. The data analysis technique used is qualitative and quantitative descriptive. The results of development research carried out by researchers related to Mobile AR media with display aspects with 17 indicators obtaining good category. Whereas in the programming aspect, seven indicators are good category. So, the Mobile AR media validation results are good category. Biological material in the application with AR with content aspects with eight indicators are very good category. Whereas in the learning aspect, which consists of 16 indicators, in the good/valid category. The material in this category is worthy of being tested in the field. Based on descriptive statistics, the pre-test and post-test proved to be higher. We discuss these results and its implications.